Comparison of endoscopic variceal ligation and pericardial devascularization in treatment of portal hypertension - BAI Lan (Linchuang Gandanbing Zazhi, 2014)
ObjectiveTo compare the clinical efficacy of endoscopic variceal ligation versus pericardial devascularization in the treatment of portal hypertension. MethodsThe clinical data of 101 cirrhotic patients with gastroesophageal varices and variceal hemorrhage from January 2010 to January 2012 were analyzed. Fifty-three patients received endoscopic variceal ligation, and forty-eight patients received pericardial devascularization. Postoperative changes in liver function and hypersplenism were compared between the two groups. The rate of rehaemorrhagia and incidence of postoperative complications after surgery were compared as well. Continuous data were expressed as mean±SD, and categorical data were expressed as number of cases or percentage. Comparison of continuous data between the two groups was made by independent-samples t test, and comparison of categorical data was made by chi-square test. ResultsAfter surgery, the variceal ligation group showed no significant changes in liver reserve function, while the liver reserve function and albumin level were significantly decreased in the pericardial devascularization group (t=2512，P＜0.05). There were no significant changes in the counts of white blood cells and platelets in the endoscopic variceal ligation group after surgery (P＞0.05), but significant increases in the counts of white blood cells and platelets were detected in the pericardial devascularization group (P＜0.05). The rates of postoperative haemorrhage in the two groups were: 3 months, 7.5% vs 62% (χ2 = 0.066，P＞0.05), 6 months, 7.5% vs 8.3% (χ2 = 0.021, P＞0.05), and 1 year, 9.4% vs 8.3% (χ2 = 0.038，P＞0.05). The incidence rates of postoperative complications in the two groups were 24.5% and 50%, respectively (χ2 = 7.040, P＜0.05). ConclusionCompared with pericardial devascularization, endoscopic variceal ligation causes fewer microlesions, preserves liver function, and leads to a lower incidence of postoperative complications. However, if hypersplenism is observed in the cirrhotic patients with gastroesophageal varices and variceal hemorrhage, pericardial devascularization can be used to control the hypersplenism and prevent esophageal hemorrhage.